113k views
6 votes
4x-3y = 12 and 3x+2y =6

1 Answer

13 votes

Answer:

x = 42/17

y = -12/17

Explanation:

4x - 3y = 12

3x + 2y = 6

use the elimination method (definition at the bottom of the page)

multiply both sides of the equation 4x - 3y = 12 by 2

8x - 6y = 24

multiply both sides of the equation 3x + 2y = 6 by 3

9x + 6y = 18

now, add the two equations:

17x = 42

x = 42/17

now, plug this into the equation 3x + 2y = 6

126/17 + 2y = 6

2y = -24/17

y = -12/17

4x-3y = 12 and 3x+2y =6-example-1
User Kjonsson
by
5.7k points